Higher Order Thinking Skill (HOTS) through STEAM Learning for Early Childhood - Aryani, Nini; Rizka, Nelti; Suparmi, Suparmi; Artamevia, Fadya; Nazli, Nur Liyana Mohd (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
The importance of Higher Order Thinking Skills (HOTS) in early childhood education is undeniable because it can to prepare early childhood to be able to think in applying and processing the information received to find solutions and even answers to problems that arise. This based on children's rights and Bloom's taxonomy theory regarding higher-order thinking. This study aimed to analyze Higher Order Thinking Skills through STEAM learning which implemented to early childhood in Kindergarten. This study using a qualitative approach use descriptive data in the form of written or oral sentences from observed behavior. Data were collected through in-depth interviews with kindergarten teachers and documentation of learning process. The data analysis techniques used are data reduction, data presentation and conclusions. The results of the study showed that Higher Order Thinking Skills (HOTS) through STEAM (Science, Technology, Engineering, Art, and Mathematics) learning has been carried out dan can encourage students to think creatively by creating media that is interesting for children and in accordance with their learning styles; designing STEAM activities or projects while playing so as to encourage students to develop problem-solving skills. STEAM learning can be done through direct experience and game-based learning. The conclusion of this study is that high order thinking skill learning through STEAM has begun to be carried out in early childhood. This study suggests that further researchers can to develop learning models and media through STEAM to improve high order thinking in early childhood.